Development of a Healthy and Sustainable Food Availability Inventory (HSFAI): an assessment of Washington, DC, grocery stores. Issue 3 (4th May 2019) - Lupolt, Sara; Buczynski, Amanda; Zota, Ami R; Robien, Kim
ABSTRACT: The objective of this study was to expand an existing food environment measurement tool to also evaluate the availability and price of sustainably produced indicator foods (SPIF) in grocery stores in the District of Columbia. A Healthy Sustainable Food Availability Inventory was developed to assess the availability of organically produced and plant-based protein foods as SPIF, and was piloted in 46 grocery stores. Availability and price of SPIF items did not vary significantly by ward. Organic foods were more expensive than their conventional counterparts. This pilot project demonstrates the feasibility of assessing access to SPIF items in the marketplace, although further development and testing of the instrument in other food retail categories is needed.